2015
DOI: 10.1038/srep07584
|View full text |Cite
|
Sign up to set email alerts
|

Strong-field plasmonic photoemission in the mid-IR at <1 GW/cm2 intensity

Abstract: We investigated nonlinear photoemission from plasmonic films with femtosecond, mid-infrared pulses at 3.1 μm wavelength. Transition between regimes of multi-photon-induced and tunneling emission is demonstrated at an unprecedentedly low intensity of <1 GW/cm2. Thereby, strong-field nanophysics can be accessed at extremely low intensities by exploiting nanoscale plasmonic field confinement, enhancement and ponderomotive wavelength scaling at the same time. Results agree well with quantum mechanical modelling. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 36 publications
3
35
0
Order By: Relevance
“…The nanowire tip is surrounded by vacuum (index of refraction n = 1) and the real and imaginary parts of the wavelength-dependent dielectric functions of gold were taken from the work of Johson and Christy. 33 A perfectly matched layer boundary condition with a thickness of 1.2 µm is applied to minimize reflections of outgoing fields at the boundary of the simulation region. The angles between the facets of the nanowire are modeled by taking into account the FCC crystal structure of gold.…”
Section: Resultsmentioning
confidence: 99%
“…The nanowire tip is surrounded by vacuum (index of refraction n = 1) and the real and imaginary parts of the wavelength-dependent dielectric functions of gold were taken from the work of Johson and Christy. 33 A perfectly matched layer boundary condition with a thickness of 1.2 µm is applied to minimize reflections of outgoing fields at the boundary of the simulation region. The angles between the facets of the nanowire are modeled by taking into account the FCC crystal structure of gold.…”
Section: Resultsmentioning
confidence: 99%
“…The use of nanostructures as 'spectroscopic enhancers' is getting a growing interest for several applications in spectroscopy, microscopy and sensing [1][2][3]. Many theoretical and experimental works have demonstrated that when a substrate is irradiated with a laser after NPs have been deposited on its surface, the laser electromagnetic field is locally enhanced and a measurable current due to electron field emission is induced even at relatively low irradiances (around 1 GW cm -2 ) [4][5][6]. The coupling between the laser electromagnetic field and the surface plasmons of the NPs in contact with a flat surface substrate has been investigated deeply in recent years [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Strong-field photoemission was subsequently observed by Teichmann et al [106] also in plasmonic films under exposition to femtosecond, mid-infrared pulses provided by an OPCPA source at 3.1 µm. Tunneling emission was here demonstrated at the considerably low intensity of ∼1 GW/cm 2 , with the localized plasmon field being responsible for an extension of the photoelectron energy spectrum up to two orders of magnitude.…”
Section: Photoelectron Spectroscopymentioning
confidence: 84%